Social Capital and the U.S. College Experiences of International Student-Athletes and Non-Athletes - Forbes-Mewett, Helen; Pape, Madeleine (Journal of International Students, 2019)
This study shifts the tendency to focus on international students’ negative experiences of undertaking education in a host country to a group that enjoys an elevated level of support. By looking at international student-athletes compared with non-athletes, it is shown how the former group experiences the benefits of social capital. Insights relating to international student-athletes in the US reveal strong and ongoing support from coaches and teammates. It is shown that international student-athletes have far greater support structures compared with international non-athletes. In doing so, this study presents a new perspective to debates on what higher education institutions in host countries can do to support their international student populations.